Effect of acute fentanyl treatment on synaptic plasticity in the hippocampal CA1 region in rats - Tian, Hai; Xu, Yueming; Liu, Fucun; Wang, Guowei; Hu, Sanjue (Frontiers in Pharmacology, 2015)
Postoperative cognitive dysfunction (POCD), mainly characterized by short-term decline of learning and memory, occurs after operations under anesthesia. However, the underlying mechanisms are poorly understood. The μ-opioid receptors (MOR) are highly expressed in interneurons of hippocampus, and is believed to be critical for the dysfunction of synaptic plasticity between hippocampal neurons. Therefore, we investigated the effect of fentanyl, a strong agonist of μ-opioid receptors and often used for anesthesia and analgesia in clinical settings, on hippocampal synaptic plasticity in the Schaffer-collateral CA1 pathway during acute exposure and washout in vitro. Our results revealed that acute fentanyl exposure (0.01, 0.1, 1 μM) dose-dependently increased the field excitatory postsynaptic potentials (fEPSPs), which was prevented by pre-administration of picrotoxin (50 μM) or MOR antagonist D-Phe-Cys-Tyr-D-Trp-Orn-Thr-Phe-Thr-NH2 (CTOP, 10 μM). While fentanyl exposure-increased fEPSPs amplitude was prevented by picrotoxin (an inhibitor of γ-aminobutyric acid receptor (GABAR)) treatment or fentanyl washout, pretreatment of picrotoxin failed to prevent the fentanyl-impaired long-term potentiation (LTP) of synaptic strength as well as the fentanyl-enhanced long-term depression (LTD). These results demonstrated that fentanyl acute exposure and washout increases hippocampal excitability in the Schaffer-collateral CA1 pathway, depending on disinhibiting interneurons after MOR activation. In addition, fentanyl acute exposure and washout modulated synaptic plasticity, but the inhibitory activation was not critical. Elucidating the detailed mechanisms for synaptic dysfunction after fentanyl exposure and washout may provide insights into POCD generation after fentanyl anesthesia.